Family support in the management of diabetes patients' perspectives from Limpopo province in South Africa - M. H. Mphasha; T. M. Mothiba; L. Skaal (BMC, 2022)
Abstract Background Family support is linked with improved diabetes outcomes, whereas lack thereof is associated with complications. Living together with people in the same household doesn't guarantee support in diabetes management. Hence it is critical to comprehend patient's lived experiences regarding family support. Objectives To explore family support in diabetes management. Methodology Qualitative method and phenomenological exploratory descriptive design were used to collect data from 17 patients with 6 months or more living with diabetes and getting treatment in clinics of Senwabarwana, Limpopo province. Purposive sampling was used to select participants. One-on-one interviews were conducted using voice recorders and field notes for non-verbal cues were observed. Unstructured interview guide with principal question which enabled probing was used. Data were analysed using 8 Steps of Tesch's inductive, descriptive, and open coding technique. Trustworthiness was ensured. Results Participants get support from family members with regards to food, exercise, and collection of medication. Diabetic men with sexual dysfunction also reported getting similar support from their wives whereas, in contrary diabetic women do not get sufficient supports from their husbands. Loss of income among diabetic men has been reported as a source of martial conflicts and unsatisfactory support from wives. Conclusion Family members of diabetic patients collect medication for patients, including cooking and serving meals to them. Wives of diabetic men outpace husbands of diabetic women in responsiveness to the health needs of their partners, respectively. Diabetic men with impaired sexual function get support from their wives, whilst female patients do not get similar support from their husbands. On the other hand, patients who lost income get inadequate spousal support, which compromises diabetes management and adherence to treatment. This study identifies gender disparities in spousal support as crucial issue requiring an urgent attention, hence the need for gender-biased family-centred diabetes care.